Effects of three feed attractants on the growth performance and meat quality of the largemouth bass (Micropterus salmoides) - Yue, Yuhua; Chen, Mingshi; Bao, Xiaoxue; Yu, Yingying; Shi, Wei; Kumkhong, Suksan; Liu, Yuhong; Yang, Ying; Yu, Hui (Frontiers in Marine Science, 2022)
The trial was conducted to investigate the effects of limonene, allicin and betaine supplementation in low fish meal (FM) diet on growth performance, antioxidant capacity, meat quality and intestinal health in largemouth bass (M. salmoides). The biting-balls test and feeding trial were successively conducted. For the one, the results of the biting-ball test showed that with the increase of the concentration of the three attractants, the attracting effect firstly increased, then decreased, and the effect reached maximum at 0.2% concentration. (P < 0.05). Further, a 9-week feeding trial was conducted using five diets, including a basal diet with 30% and 40% fish meal without attractant, 30% fish meal supplemented with 0.2% limonene, 0.2% allicin or 0.2% betaine (the diets were named FM30, FM40, FM30 + L, FM30 + A, FM30 + B, respectively). The results demonstrated that adding limonene, allicin and betaine at concentration of 0.2% to the low fish meal feed could improve final body weight, weight gain rate, and specific growth rate of M. salmoides but only in 4 weeks (P > 0.05). Besides, dietary supplementation with attractants could significantly reduce the content of MDA in serum and liver, and increase the activity of GSH in liver (P < 0.05). Compared with FM30 group, the supplementation with limonene, allicin or betaine diet had higher pH, redness (a*), yellowness (b*) (P > 0.05), and lower refrigeration loss, cooking loss values (P < 0.05). Furthermore, supplementation with attractants groups had higher values for villus height, lamina propria, crypt depth, submucous layer, and serous layer (P < 0.05). Taken together, these results indicated that limonene, allicin and betaine had a time effect on the growth performance, and could improve antioxidant capacity, meat quality and intestinal health of M. salmoide.